2021
DOI: 10.3389/fnins.2021.771511
|View full text |Cite
|
Sign up to set email alerts
|

Psychobiological Consequences of Childhood Sexual Abuse: Current Knowledge and Clinical Implications

Abstract: A large body of research has documented the long-term harms of childhood sexual abuse (CSA) on an individual’s emotional-adaptive function and mental health. Recent studies have also provided evidence of the biological impact of CSA, implicating specific alterations in many systems, including the endocrine and immune systems, and in DNA and chromatin, in the pathogenesis of medical disorders. Although the effects of CSA are often examined with regard to the general impact of early-life traumatic experiences, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…93 Finally, ACEs have been linked to reduced volume in the amygdala, hippocampus, and anterior cingulate cortex-regions of the brain responsible for emotion regulation and self-control-along with impairments in executive functions, which are indicative of impaired memory and cognitive flexibility. 6,25,84,[94][95][96] The potential impact of sexual abuse on neurocognitive function could be accounted for by the known cognitive function-altering effects of ACEs on various pathways, such as inflammation , 66,88,97 alterations in the HPA-axis, 97 and disruptions in the cortical and subcortical regions . 98 Likewise, NLEs have a plethora of detrimental effects on the same pathways, including the IRS, 99,100 oxidative stress pathways, 101 HPA-axis function, 102 and methylation processes.…”
Section: Different Pathways May Explain the Effects Of Aces/nles On T...mentioning
confidence: 99%
“…93 Finally, ACEs have been linked to reduced volume in the amygdala, hippocampus, and anterior cingulate cortex-regions of the brain responsible for emotion regulation and self-control-along with impairments in executive functions, which are indicative of impaired memory and cognitive flexibility. 6,25,84,[94][95][96] The potential impact of sexual abuse on neurocognitive function could be accounted for by the known cognitive function-altering effects of ACEs on various pathways, such as inflammation , 66,88,97 alterations in the HPA-axis, 97 and disruptions in the cortical and subcortical regions . 98 Likewise, NLEs have a plethora of detrimental effects on the same pathways, including the IRS, 99,100 oxidative stress pathways, 101 HPA-axis function, 102 and methylation processes.…”
Section: Different Pathways May Explain the Effects Of Aces/nles On T...mentioning
confidence: 99%
“…93 Finally, ACEs have been linked to reduced volume in the amygdala, hippocampus, and anterior cingulate cortex-regions of the brain responsible for emotion regulation and self-control-along with impairments in executive functions, which are indicative of impaired memory and cognitive flexibility. 6,25,84,[94][95][96] The potential impact of sexual abuse on neurocognitive function could be accounted for by the known cognitive function-altering effects of ACEs on various pathways, such as inflammation, 66,88,97 alterations in the HPA-axis, 97 and disruptions in the cortical and subcortical regions. 98 Likewise, NLEs have a plethora of detrimental effects on the same pathways, including the IRS, 99,100 oxidative stress pathways, 101 HPA-axis function, 102 and methylation processes.…”
Section: Different Pathways May Explain the Effects Of Aces/nles On T...mentioning
confidence: 99%
“…Two meta-analyses revealed that childhood SA is estimated at 18% for girls and 7.9% for boys (Pereda et al, 2009; Stoltenborgh et al, 2011) while lifetime SA is estimated at as high as 23% for men and 37% for women (Chiu et al, 2013; Smith et al, 2018). There is extensive literature that shows that SA increases an individual’s vulnerability to a range of physical, psychological, and behavioral impairments (Atabay & Arman, 2019; Gladstone et al, 2004; Guiney et al, 2022; Kendall-Tackett et al, 1993; Lang et al, 2004; Lo Iacono et al, 2021) and that childhood SA is a key risk factor in the development of psychiatric disorders in adulthood (Read, 1997; Wurr & Partridge, 1996).…”
Section: Sexual Abuse (Sa)mentioning
confidence: 99%